2008
DOI: 10.1099/vir.0.2008/002170-0
|View full text |Cite
|
Sign up to set email alerts
|

Hibiscus chlorotic ringspot virus coat protein inhibits trans-acting small interfering RNA biogenesis in Arabidopsis

Abstract: Many plant and animal viruses have evolved suppressor proteins to block host RNA silencing at various stages of the RNA silencing pathways. Hibiscus chlorotic ringspot virus (HCRSV) coat protein (CP) is capable of suppressing the transiently expressed sense-RNA-induced posttranscriptional gene silencing (PTGS) in Nicotiana benthamiana. Here, constitutively expressed HCRSV CP from transgenic Arabidopsis was found to be able to rescue expression of the silenced GUS transgene. The HCRSV CP-transgenic Arabidopsis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 53 publications
0
8
0
2
Order By: Relevance
“…155 genes coexpressed with ARF3 and ARF4 involved twenty-five abiotic stress response-related genes, such as DREB2C [44], DWD ( DDB1-binding WD40 protein ) [45], ascorbate peroxidase 1 [46], glutathione S-transferase [47], and RD21B [48] (Supplemental Table 4). Thegenes also included ta-siRNA pathway-related genes, such as RDR6 , TAS3 , other TAS genes, and ta-siRNA target genes [49]. Sixty-four of the 155 genes possessed an ARF binding motif (tgtctc) [50] in the promoter region within 1kb upstream of the start codon (Supplemental Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…155 genes coexpressed with ARF3 and ARF4 involved twenty-five abiotic stress response-related genes, such as DREB2C [44], DWD ( DDB1-binding WD40 protein ) [45], ascorbate peroxidase 1 [46], glutathione S-transferase [47], and RD21B [48] (Supplemental Table 4). Thegenes also included ta-siRNA pathway-related genes, such as RDR6 , TAS3 , other TAS genes, and ta-siRNA target genes [49]. Sixty-four of the 155 genes possessed an ARF binding motif (tgtctc) [50] in the promoter region within 1kb upstream of the start codon (Supplemental Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…The alteration of the ta‐siRNA pathway has been reported in many plant–virus combinations and has been suggested to be involved in symptom development (Lacombe et al ., 2010; Meng et al ., 2008; Shivaprasad et al ., 2008). In this study, we found that the ta‐siRNA pathway may be affected in RSV‐infected rice.…”
mentioning
confidence: 99%
“…A biologically active cDNA clone of HCRSV p223 has been obtained previously [3]. The HCRSV CP (p38) [3] is a gene silencing suppressor [12]. In addition, p27 and its other in-frame isoforms (p25 and p22.5) affect symptom expression and potentiate Carmoviruses movement in kenaf ( Hibiscus cannabinus L.) [13].…”
Section: Introductionmentioning
confidence: 99%